Ceramic rock plate preparation method based on secondary material distribution and ceramic rock plate

Ceramic rock slabs are prepared by preset base fabric performance differences standards, and low-priced raw materials for solid waste are used to reduce costs, solving the problem of high production costs of ceramic rock slabs, and achieving dual optimization of performance and cost of ceramic rock slabs.

CN119191829APending Publication Date: 2024-12-27JIANGXI WONDERFUL CERAMICS CO LTD +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411236581.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The production cost of ceramic rock slabs is relatively high because low-priced raw materials for solid waste cannot be directly used for preparation, resulting in limited raw material selection and utilization.

Method used

Using the ceramic rock slab preparation method based on secondary fabrics, the base and fabric formula powder are prepared by preset base fabric performance differences standards, and pressing and forming to ensure the flatness and performance consistency of the base layer and fabric layer. , use low-priced raw materials for solid waste to reduce costs.

Benefits of technology

It effectively reduces the production cost of ceramic rock slabs, while ensuring product performance and surface smoothness, solving the problem that low-priced solid waste raw materials cannot be used directly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191829A_ABST
    Figure CN119191829A_ABST
Patent Text Reader

Abstract

The invention provides a ceramic rock plate preparation method based on secondary material distribution and a ceramic rock plate. The ceramic rock plate preparation method based on secondary material distribution comprises the following steps: preparing backing material formula powder and surface material formula powder according to a preset backing material and surface material performance difference standard; distributing the base material formula powder, pressing the base material formula powder to obtain a base material layer, and pressing the surface material formula powder to obtain a surface material layer; the bottom material layer and the surface material layer are combined and then subjected to compression molding, and the ceramic rock plate is obtained through firing. The overall performance of the backing material and the surface material formula is controlled by presetting the backing material and surface material performance difference standard, then the performance of the ceramic rock plate is guaranteed while the solid waste low-price raw materials are used for the backing material layer, and the backing material layer and the surface material layer are guaranteed to be flat by conducting secondary distribution on the backing material formula powder and the surface material formula powder; the performance of the ceramic rock plate is further ensured, and the production cost of the ceramic rock plate is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ceramic technology, and in particular to a ceramic rock slab preparation method based on secondary distribution and a ceramic rock slab. Background Art

[0002] Due to the large size of ceramic rock slabs, the molding, decoration, firing, and processing production processes all have strict requirements on the strength, sintering performance, composition, and square structure of the blanks, which results in the blank cost of ceramic rock slabs being much higher than the blank cost of ordinary ceramic tiles. In addition, since ceramic rock slabs have strict requirements on raw materials, they are required to have low porosity after firing, a smooth surface without pinholes, pits, prickly heat spots and other surface defects, which greatly limits the selection and utilization of raw materials. Therefore, low-cost solid waste raw materials generally cannot be used directly to prepare ceramic rock slabs, resulting in higher production costs for ceramic rock slabs.

[0003] Therefore, the prior art has defects and needs to be improved and developed. Summary of the invention

[0004] The technical problem to be solved by the present invention is that, in response to the above-mentioned defects of the prior art, a ceramic rock slab preparation method and a ceramic rock slab based on secondary distribution are provided, aiming to solve the problem in the prior art that low-cost solid waste raw materials cannot generally be used directly to prepare ceramic rock slabs, resulting in high production costs of ceramic rock slabs.

[0005] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0006] The first aspect of the present application provides a method for preparing a ceramic rock slab based on secondary distribution, wherein the method comprises:

[0007] Prepare base material formula powder and fabric formula powder according to preset base material and fabric performance difference standards;

[0008] The base material formula powder is spread and then pressed to obtain a base material layer, and the surface material formula powder is pressed to obtain a surface material layer;

[0009] The base material layer and the surface material layer are combined and pressed into shape, and then fired to obtain a ceramic rock slab.

[0010] In one embodiment of the present application, the base material and fabric performance difference standard includes: the difference in volume expansion coefficient between the base material formula powder and the fabric formula powder is less than or equal to 5 / °C.

[0011] In one embodiment of the present application, the fabric formula powder is a powder between 30-80 meshes, and the powder bulk density is greater than or equal to 0.92g / cm 3 The repose angle of the fabric formula powder is less than or equal to 38 degrees; the thickness of the fabric layer is greater than or equal to 2 mm.

[0012] In one embodiment of the present application, the chemical compositions of the base material formula powder and the surface material formula powder, measured by mass percentage, both include:

[0013] Loss on ignition 5.0~5.5%, SiO2 63~65%, Al2O3 20~21%, Fe2O3 0.4~0.6%, CaO 1.5~2.0%, MgO 1.5~2.0%, K2O 2.5~3.0%, Na2O 2.0~3.0%, Li2O0.05~0.2%.

[0014] In one embodiment of the present application, the chemical composition of the base material formula powder, measured by mass percentage, includes:

[0015] Loss on ignition 5.43%, SiO2 63.52%, Al2O3 20.79%, Fe2O3 0.46%, CaO 1.92%, MgO1.62%, K2O 2.65%, Na2O 2.77%, Li2O 0.07%, impurities 0.77%.

[0016] In one embodiment of the present application, the chemical composition of the fabric formula powder, measured by mass percentage, includes:

[0017] Loss on ignition 5.33%, SiO2 63.64%, Al2O3 20.87%, Fe2O3 0.54%, CaO 1.91%, MgO1.67%, K2O 2.77%, Na2O 2.69%, Li2O 0.06%, impurities 0.52%.

[0018] In one embodiment of the present application, the difference between the base material slurry fineness required for preparing the base material formula powder and the fabric slurry fineness required for preparing the fabric formula powder is within a preset threshold range.

[0019] In one embodiment of the present application, the base material layer and the surface layer maintain uniform linear shrinkage in the same direction during firing, and the base material and surface layer performance difference standard also includes: the shrinkage rate difference between the base material layer and the surface layer is less than or equal to 0.05%.

[0020] In one embodiment of the present application, the base material and fabric performance difference standard also includes: the difference in sintering termination temperature points between the base material formula powder and the fabric formula powder is less than or equal to 3°C.

[0021] A second aspect of the present application provides a ceramic rock slab, wherein the ceramic rock slab is prepared by the ceramic rock slab preparation method based on secondary distribution as described above.

[0022] The present invention discloses a method for preparing a ceramic rock slab based on secondary distribution and a ceramic rock slab, the method for preparing a ceramic rock slab based on secondary distribution comprising: preparing a base material formula powder and a fabric formula powder according to a preset base material and fabric performance difference standard; distributing the base material formula powder and pressing it to obtain a base material layer, and pressing the fabric formula powder to obtain a fabric layer; combining the base material layer and the fabric layer and then pressing and forming, and firing to obtain a ceramic rock slab. The present invention controls the overall performance of the base material and the fabric formula by presetting the base material and fabric performance difference standard, thereby achieving the use of low-cost solid waste raw materials for the base material layer while ensuring the performance of the ceramic rock slab, and ensures the flatness of the base material layer and the fabric layer by secondary distribution of the base material formula powder and the fabric formula powder, further ensuring the performance of the ceramic rock slab, and reducing the production cost of the ceramic rock slab. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a flow chart of a preferred embodiment of the method for preparing ceramic rock slabs based on secondary distribution in the present invention. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0025] In order to solve the problem that low-cost solid waste raw materials cannot generally be used directly to prepare ceramic rock slabs, resulting in high production costs of ceramic rock slabs, the embodiment of the present application applies low-cost solid waste raw materials to the base material layer of the green body to reduce production costs and minimize the cost of the green body.

[0026] The present invention provides a method for preparing a ceramic rock plate based on secondary distribution, such as Figure 1 As shown, the method for preparing ceramic rock slabs based on secondary distribution includes:

[0027] Step S100: preparing base material formula powder and fabric formula powder according to a preset base material and fabric performance difference standard.

[0028] With the upgrade of the specifications of rock slabs to 800*2400, 900*2600, 1200*2400, and 1500*3000, the more uniform the sintering degree of the green body and the smaller the stress of the brick green body can ensure the cutting and deep processing performance of the rock slab. The density and uniformity of the green body is mainly affected by the diversity of the appearance and shape of the powder particles, which include bonding type, strip or rod type, apple type, fine powder, etc. Too many irregular coarse particles will lead to poor fluidity of the powder, which in turn affects the flatness of the material layer of the material car. Small pits, wavy patterns, rough and uneven defects are prone to appear on the surface of the green body, and it cannot be pressed into a uniform, flat and smooth green surface. However, various process combinations such as glaze pouring (dry particles), glaze spraying (dry particles), digital molds, digital effects, etc., create the delicate glaze effects of high-end skin glaze and velvet products, which all need to be decorated on a uniform, flat and smooth green surface. Therefore, the control of powder is particularly important.

[0029] The blank part of the embodiment of the present application is divided into two parts, namely, the base material and the surface material. The base material and the surface material have different requirements on the quality of the raw materials. Since the surface material layer directly affects the effect of the glazing layer or the decorative layer, the smoothness and fineness of the surface material layer after firing are extremely high, and it is necessary to fully meet the raw material quality requirements of conventional ceramic rock slabs. The base material can be selected from raw materials with different whiteness and raw materials that are easy or not easy to produce prickly heat according to the difference in whiteness with the surface material, such as polishing squeezed mud, raw material squeezed mud, rotten brick crushed raw materials with low-temperature glaze, and purchased raw materials that are easy or not easy to expand after sintering.

[0030] The embodiments of the present application control the overall performance of the base material and surface material formulas, such as the expansion coefficient of the base material formula powder (difference in volume expansion coefficient ≤ 5 / °C), shrinkage performance (total shrinkage difference ≤ 0.05%), and sintering termination temperature point (difference in sintering termination temperature point ≤ 3 degrees). If these standards are met, the introduction and use can be considered. The mineral composition of the base material and surface material raw materials is selected to be as close as possible without being completely consistent. The closer they are, the more conducive it is to reducing the difficulty of adjusting the formula and ensuring the various physical properties of the product.

[0031] The preset base material and surface performance difference standards in the embodiment of the present application can ensure the performance of the ceramic rock slab while utilizing low-cost raw materials from solid waste.

[0032] In the embodiment of the present application, the base material and surface material performance difference standard includes: the difference in volume expansion coefficient between the base material formula powder and the surface material formula powder is less than or equal to 5 / °C.

[0033] Specifically, if the linear expansion coefficient of the base material layer is less than the linear expansion coefficient of the surface layer, the brick shape is concave downward as a whole; if the linear expansion coefficient of the base material layer is greater than the linear expansion coefficient of the surface layer, the brick shape is convex upward as a whole; if the linear expansion coefficient of the base material layer is ≈ the linear expansion coefficient of the surface layer, the brick shape is relatively flat as a whole. In the embodiment of the present application, the difference in the volume expansion coefficient between the base material formula powder and the surface formula powder is controlled to be less than or equal to 5 / ℃, that is, the difference in linear expansion coefficient is ≤0.15E-06, which is more appropriate. As shown in Table 1.

[0034]

[0035] Table 1

[0036] In one embodiment of the present application, the fabric formula powder is a powder between 30-80 meshes, and the powder bulk density is greater than or equal to 0.92g / cm 3 The repose angle of the fabric formula powder is less than or equal to 38 degrees; the thickness of the fabric layer is greater than or equal to 2 mm.

[0037] Since the embodiments of the present application involve the matching problem of the physical and chemical properties of the base fabric after secondary cloth, the flatness of the fabric before fabric molding is relatively high, so the flowability of the fabric powder is required to be high, and the powder particle size is required to basically achieve a spherical effect, which can be controlled by the repose angle (≤38 degrees). If the fluidity is poor, it is very easy to cause differences in the thickness of the fabric, resulting in abnormal matching of the base fabric after sintering, mainly manifested in various phenomena such as brick-shaped waves, arched edges or corners. The smaller the repose angle of the molding powder, the better the flatness of the fabric molding.

[0038] The thickness ratio of the base fabric can be adjusted as needed, and the thickness of the product fabric layer generally needs to be controlled to be ≥2mm, so that it is easier to control during fabric molding. The secondary fabric homogeneous rock slab of the embodiment of the present application maintains the same physical and chemical properties as the full-body rock slab, the finished product has a straight vertical long side, and the fired green body has excellent deep processing performance characteristics.

[0039] Specifically, the fabric formula powder is a powder between 30-80 mesh, and the powder bulk density is ≥ 0.92g / cm 3 , angle of repose ≤38, the powder within this range is relatively uniform in particles and has good fluidity. When spreading the powder on the surface layer, it can be evenly and flatly spread on the material layer without ripples, and the surface of the pressed body is flat and smooth. The thickness of the surface layer powder in the body is controlled at ≥2mm. A certain thickness of the surface layer can effectively seal the body defects of the lower base material, such as prickly heat, bubbles, impurities, etc., so that these defects are not exposed on the surface of the body, which can meet the glaze effect of the product. During the process, the surface powder needs to be sieved, that is, a multi-layer disc vibrating screen with a 30-mesh screen is used to remove coarse particles larger than 0.6mm, and a 80-mesh screen is used to sieve out fine powder of 0.2mm.

[0040] In one embodiment of the present application, the chemical compositions of the base material formula powder and the surface material formula powder, measured by mass percentage, both include:

[0041] Loss on ignition 5.0~5.5%, SiO2 63~65%, Al2O3 20~21%, Fe2O3 0.4~0.6%, CaO 1.5~2.0%, MgO 1.5~2.0%, K2O 2.5~3.0%, Na2O 2.0~3.0%, Li2O0.05~0.2%.

[0042] Specifically, the base material formula powder is infinitely close to the surface material formula powder, which can reduce the total billet cost by 15-20%. The aluminum content of the two differs by 0.2%, the calcium content differs by 0.15%, the magnesium content differs by 0.15%, and the sodium content differs by 0.15%. In this way, the base material layer and the surface material layer can react synchronously and linearly and uniformly during the firing stage.

[0043] In a specific embodiment of the present application, the chemical composition of the base material formula powder, measured by mass percentage, includes:

[0044] Loss on ignition 5.43%, SiO2 63.52%, Al2O3 20.79%, Fe2O3 0.46%, CaO 1.92%, MgO1.62%, K2O 2.65%, Na2O 2.77%, Li2O 0.07%, impurities 0.77%.

[0045] In a specific embodiment of the present application, the chemical composition of the fabric formula powder, measured by mass percentage, includes:

[0046] Loss on ignition 5.33%, SiO2 63.64%, Al2O3 20.87%, Fe2O3 0.54%, CaO 1.91%, MgO1.67%, K2O 2.77%, Na2O 2.69%, Li2O 0.06%, impurities 0.52%.

[0047] For the fabric formula powder in this application, whiteness and strength consistency are taken into consideration, and only slight adjustments are made to the main clay types and proportions relative to the base material formula powder. Through simulation calculation, the corresponding mass fractions of new materials that need to be added to the base material layer with the same chemical composition can be obtained, such as crushed porcelain powder, crushed rollers, low-priced black talc, wollastonite raw materials, edge grinding recycled materials, albite powder, etc.

[0048] like Figure 1 As shown, the method for preparing ceramic rock slabs based on secondary distribution also includes:

[0049] Step S200, spreading the base material formula powder and then pressing it to obtain a base material layer, and pressing the surface material formula powder to obtain a surface material layer.

[0050] Specifically, the embodiment of the present application adopts a process of lightly pressing the base material and then lightly pressing the surface material again, that is, the base material is pressed one by one, and the surface material is pressed one by one, and the pressing pressure is controlled to be 1MPa or above, and finally the molding and pressing are performed. The main purpose of lightly pressing the base material after laying the base material and the surface material is to ensure that the base material and the surface material are smooth. At present, the molding of ceramic rock slabs generally adopts the large-tonnage belt-top pressing machine imported from Italy by System, which is a process of feeding multiple rollers at the same time and forming once. This kind of fabric forming process often affects the local excessive thickness difference of the whole slab due to problems such as slight agglomeration and agglomeration of the powder. This is a fatal defect for the production of ceramic rock slabs using base and surface material blanks, which is mainly reflected in the excessive deformation and size difference after firing.

[0051] In one embodiment of the present application, the difference between the base material slurry fineness required for preparing the base material formula powder and the fabric slurry fineness required for preparing the fabric formula powder is within a preset threshold range.

[0052] Specifically, the fineness of the mud can reflect the firing temperature and shrinkage rate of the green body to a certain extent during the kiln firing stage. Within a certain range, the fineness of the mud is fine, and the firing temperature of the green body will change towards a lower temperature. There are two ways to reflect the fineness of the mud. One is to test the mud with a 325-mesh standard sieve, and the other is to observe the particle size distribution of D50 and D90 through particle size analysis to determine whether the particle size of the mud is infinitely close. The particle size analysis of the mud is shown in Table 2.

[0053] name D50μm D10μm D25μm D75μm D90μm D(4.5)μm Fabric layer slurry 10.90 1.60 3.99 23.67 41.80 17.52 Base layer slurry 10.67 1.47 3.60 22.24 41.52 16.59

[0054] Table 2

[0055] In addition, the screening of the green body slurry of the bottom material layer of the embodiment of the present application has certain requirements. In the conventional method, the slurry to powder spraying process is screened three times, which are 90 mesh screen, 100 mesh screen, and 90 mesh screen in sequence, while high-end rock slabs need to effectively control the defects of the green body. Therefore, the green body slurry of the bottom material layer of the embodiment of the present application is screened four times to the powder spraying process, which are 90 mesh screen, 110 mesh screen, 110 mesh screen, and 100 mesh screen in sequence. Its function is to screen out harmful coarse particles in the raw materials, such as mica flakes, impurities, wood chips, fibers and other substances, and at the same time prevent the screen from being damaged, resulting in incomplete screening of the slurry.

[0056] The embodiments of the present application also require enhanced iron removal, the purpose of which is to remove as much fine iron-containing mineral particles as possible in the slurry, increase the whiteness of the green body, and effectively prevent the raw materials from bringing in low-temperature or high-temperature particles that cannot be completely reacted or melt prematurely in the processing slurry during the firing process, thereby causing defects such as blisters, impurities, bulging, or difficulty in sintering.

[0057] like Figure 1 As shown, the method for preparing ceramic rock slabs based on secondary distribution also includes:

[0058] Step S300: Combining the base material layer and the surface layer, pressing and forming them, and firing them to obtain a ceramic rock slab.

[0059] In an embodiment of the present application, the base material layer and the surface layer maintain uniform linear shrinkage in the same direction during firing, and the base material and surface layer performance difference standard also includes: the shrinkage rate difference between the base material layer and the surface layer is less than or equal to 0.05%.

[0060] Specifically, in theory, it is hoped that the formula of the base material layer and the formula of the surface layer will shrink the same when sintered, but in actual production, they can only be infinitely close. When the shrinkage of two different formulas is infinitely close, the tension or stress on the body is the smallest. The final shrinkage is generally calculated by the shrinkage rate. Regardless of whether the shrinkage of the surface layer and the base material layer exceeds a certain range, the stress on the body is uneven, and the brick shape will appear convex or concave. The firing stage determines the quality of the product. During the firing stage, the surface layer and the base material layer maintain uniform linear shrinkage in the same direction, and the final total shrinkage difference between the two is ≤0.05%. Sintering is a general term for the densification process and phenomenon of ceramic green bodies at high temperatures. With the increase of temperature and the extension of time, solid particles move closer to each other, grains grow, and voids (pores) and grain boundaries gradually decrease. Through the transfer of substances, the total volume shrinks and the density increases, and finally becomes a hard polycrystalline sintered body with multiple microstructures. This phenomenon is called sintering. Among the sintering characteristics, the water absorption value is the smallest, the shrinkage rate is the largest, and the body density is the largest.

[0061] As shown in Table 3.

[0062]

[0063] Table 3

[0064] In one embodiment of the present application, the base material and fabric performance difference standard also includes: the difference in sintering termination temperature points between the base material formula powder and the fabric formula powder is less than or equal to 3°C.

[0065] Specifically, during the firing stage, the green body begins to have a liquid phase at around 900°C-950°C. As the temperature further increases, the green body begins to have an initial melting point. As the liquid phase increases, the temperature further increases, and the size of the green body continues to shrink, reaching the maximum shrinkage value and the green body density value is also the maximum. Ensure that the water absorption rate of the base material and the surface material after sintering separately is close, the sintering temperature range is close, and the difference in the sintering termination temperature point is ≤3 degrees. The high temperature imager and ash melting degree detection of the sintering temperature range are shown in Table 4.

[0066]

[0067] Table 4

[0068] In the embodiment of the present application, an orthogonal test is performed on a ceramic rock slab prepared by a ceramic rock slab preparation method based on secondary distribution. Specifically, under the condition that the process glaze and the kiln are not adjusted, the bottom material layer and the surface layer powder are orthogonally tested by screening and non-screening methods, and the secondary distribution pressing body test is shown in Table 5.

[0069]

[0070] Table 5

[0071] The comparison of cost, processing performance, plain surface and glaze effect of conventional full-body rock slabs and the secondary-cloth homogeneous rock slabs of the embodiments of the present application is shown in Table 6.

[0072]

[0073] Table 6

[0074] The embodiment of the present application is applicable to the production process of various unglazed or glazed ceramic rock slab decoration, polished or unpolished products. Since the base material and the surface material have different quality requirements for raw materials, the surface material layer directly affects the brick surface effect of the glazing layer or the decorative layer, and the smoothness and fineness of the surface material layer after firing are extremely high, and the raw material quality requirements of the conventional ceramic rock slab must be fully met. The base material can select raw materials with different whiteness according to the whiteness difference requirements of the surface material, and raw materials that are easy or not easy to produce prickly heat, such as polishing squeezed mud, raw material squeezed mud, broken raw materials of rotten bricks with low-temperature glaze, and purchased raw materials that are easy or not easy to expand after sintering. At the same time, it is necessary to control the overall performance of the base material and surface material formula, such as the expansion coefficient of the powder (difference in volume expansion coefficient ≤5 / ℃), shrinkage performance (total shrinkage difference ≤0.05%), and sintering termination temperature point (sintering termination temperature point difference ≤3 degrees). If this standard is met, it can be introduced for use. The mineral composition of the base material and surface material raw materials is selected as close as possible without being completely consistent. The closer it is, the more conducive it is to reduce the difficulty of adjusting the formula and ensure the various physical properties of the product. This achieves the goal of utilizing low-cost solid waste raw materials while ensuring the performance of ceramic rock slabs.

[0075] The present invention also provides a ceramic rock slab, which is prepared by the ceramic rock slab preparation method based on secondary distribution as described above; the details are as described above.

[0076] The present invention provides a method for preparing a ceramic rock slab based on secondary distribution and a ceramic rock slab, the method for preparing a ceramic rock slab based on secondary distribution comprising: preparing a base material formula powder and a fabric formula powder according to a preset base material and fabric performance difference standard; distributing the base material formula powder and pressing it to obtain a base material layer, and pressing the fabric formula powder to obtain a fabric layer; combining the base material layer and the fabric layer and then pressing and forming, and firing to obtain a ceramic rock slab. The present invention controls the overall performance of the base material and the fabric formula by presetting the base material and fabric performance difference standard, thereby achieving the use of low-cost solid waste raw materials for the base material layer while ensuring the performance of the ceramic rock slab, and ensures the flatness of the base material layer and the fabric layer by secondary distribution of the base material formula powder and the fabric formula powder, further ensuring the performance of the ceramic rock slab, and reducing the production cost of the ceramic rock slab.

[0077] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing ceramic rock slabs based on secondary distribution, characterized in that: The method comprises: Prepare base material formula powder and fabric formula powder according to preset base material and fabric performance difference standards; The base material formula powder is spread and then pressed to obtain a base material layer, and the surface material formula powder is pressed to obtain a surface material layer; The base material layer and the surface material layer are combined and pressed into shape, and then fired to obtain a ceramic rock slab.

2. The method for preparing ceramic rock slabs based on secondary distribution according to claim 1 is characterized in that: The base material and fabric performance difference standard includes: the difference in volume expansion coefficient between the base material formula powder and the fabric formula powder is less than or equal to 5 / °C.

3. The method for preparing ceramic rock slabs based on secondary distribution according to claim 1 is characterized in that: The fabric formula powder is a powder with a mesh size of 30-80, and the powder has a bulk density greater than or equal to 0.92 g / cm 3 The repose angle of the fabric formula powder is less than or equal to 38 degrees; the thickness of the fabric layer is greater than or equal to 2 mm.

4. The method for preparing ceramic rock slabs based on secondary distribution according to claim 1, characterized in that: The chemical compositions of the base material formula powder and the surface material formula powder, calculated by mass percentage, include: Loss on ignition 5.0~5.5%, SiO2 63~65%, Al2O3 20~21%, Fe2O3 0.4~0.6%, CaO 1.5~2.0%, MgO 1.5~2.0%, K2O 2.5~3.0%, Na2O 2.0~3.0%, Li2O0.05~0.2%.

5. The method for preparing ceramic rock slabs based on secondary distribution according to claim 4 is characterized in that: The chemical composition of the base material formula powder is calculated by mass percentage and includes: Loss on ignition 5.43%, SiO2 63.52%, Al2O3 20.79%, Fe2O3 0.46%, CaO 1.92%, MgO 1.62%, K2O 2.65%, Na2O 2.77%, Li2O 0.07%, impurities 0.77%.

6. The method for preparing ceramic rock slabs based on secondary distribution according to claim 4 is characterized in that: The chemical composition of the fabric formula powder is calculated by mass percentage and includes: Loss on ignition 5.33%, SiO2 63.64%, Al2O3 20.87%, Fe2O3 0.54%, CaO 1.91%, MgO 1.67%, K2O 2.77%, Na2O 2.69%, Li2O 0.06%, impurities 0.52%.

7. The method for preparing ceramic rock slabs based on secondary distribution according to claim 1 is characterized in that: The difference between the base material slurry fineness required for preparing the base material formula powder and the fabric slurry fineness required for preparing the fabric formula powder is within a preset threshold range.

8. The method for preparing ceramic rock slabs based on secondary distribution according to claim 1, characterized in that: The base material layer and the surface layer maintain uniform linear shrinkage in the same direction during firing, and the base material and surface layer performance difference standard also includes: the shrinkage difference between the base material layer and the surface layer is less than or equal to 0.05%.

9. The method for preparing ceramic rock slabs based on secondary distribution according to claim 1, characterized in that: The base material and fabric performance difference standard also includes: the difference in sintering termination temperature between the base material formula powder and the fabric formula powder is less than or equal to 3°C.

10. A ceramic rock plate, characterized in that: The ceramic rock slab is prepared by the ceramic rock slab preparation method based on secondary distribution as described in any one of claims 1-9.

Citation Information

Patent Citations

  • Porcelain ceramic sheet and production method thereof

    CN105330296A

  • Lightweight stone-like thermal insulation veneer

    CN115231899A

  • Secondary-distribution anti-cracking pure-color brick and preparation method thereof

    CN118145961A